Pengaruh Pelayanan dan Harga terhadap Kepuasan Pelanggan di PT Setiajaya Mobilindo - Eigis Yani Pramularso (Universitas Bina Sarana Informatika, 2019)
Abstract - Increasingly tight business competition is accompanied by changes in the needs and desires of customers who always dynamically require companies to be able to adapt so that customers remain satisfied with the company's performance. Service quality and price determination offered are important parts so customer satisfaction is maintained. This study aims to determine the effect of service quality and price on customer satisfaction of PT Setiajaya Mobilindo. The population in this study were customers of PT Setiajaya Mobilindo located on Jl. Raya Tole Iskandar Depok who received body & paint services and the sample was 61 respondents taken randomly. The data analysis tool uses multiple linear regression with processing techniques using SPSS. From the results of the study it is known that service quality and price together have a significant effect on customer satisfaction. Partially service quality and price also have a significant effect on customer satisfaction. The number of R square (R2) shows service quality and price contribute 58.6% to customer satisfaction, while the rest is influenced by other factors outside of this study. Keywords: Service Quality, Price, Customer Satisfaction